Analisa Kekuatan Sambungan Baja ST 37 Dengan Variasi Ampere 120, 160, 200, Menggunakan Metode SMAW Wet Underwater Welding - Mukti, Tunjung Hari; , Dr. Agus Dwi Anggono (2017)
Objectives of the research are to investigate the welding strength of ST37 steel and to investigate the micro/macro structure of welding cross section. The welding process was conducted by using SMAW wet underwater welding. The welding of the research was connected two materials of ST37 steel with the thickness of 5 mm. The underwater welding carried out in the square water tank with the dimensions of L = 1 m, W = 0.5 m, H = 0.5 m and water level of 0.2 m. Electric current during the welding process varied from 120, 160 and 200 ampere. Micro photo is done by using Euromax photo, Holland type. While the tensile test is performed by using SANS Universal Testing Machine. Highwood HWMMT-X7 hardness machine test is used to test the hardness of welding specimens. From the micro photo, it was shown clearly that in the HAZ was found grains of perlite and ferrite, where as in the weld nugget area was dominant of Bainit ( B ), Ferrite Grain Boundary (FGB) and Martensite ( M ). The results showed that the greater the applied current generated voltage decreases and the harder the level of violence in the area weld nugget. On specimens 120 A produces a maximum voltage of 354,45 Mpa with the highest hardness of the specimen 200 A point 0 at 353,5 HVN.